Who decides? – transitions from school to adult services for and with young people with severe intellectual disabilities. Issue 7 (8th August 2020) - Jacobs, Paula; MacMahon, Kenneth; Quayle, Ethel
Abstract: The transition from school to adult services for young people with severe intellectual disabilities has been identified as an area of concern, particularly with regards to how young people can be involved in meaningful ways. Additionally, although available resources and organisational practices seem to play important roles, there seems to be a lack of understanding as to how societal influences shape the process. Our study presents case studies of three young people and their journey from school to adult services from an ecological perspective, examining the decision-making process in the context of multi-agency involvement. We suggest that each transition journey challenged conceptualisations about the involvement of young people in the decision-making process. While the practical aspects of the transitions were described as positive, barriers and limitations were identified in the wider organisational context. The only people who clearly talked about the transition in terms of the long-term future were the parents.